2008
DOI: 10.1113/jphysiol.2007.150060
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the control of muscle sympathetic nerve activity during incremental leg cycling

Abstract: We tested the hypotheses that arterial baroreflex (ABR) control over muscle sympathetic nerve activity (MSNA) in humans does not remain constant throughout a bout of leg cycling ranging in intensity from very mild to exhausting. ABR control over MSNA (burst incidence, burst strength and total MSNA) was evaluated by analysing the relationship between beat-to-beat spontaneous variations in diastolic arterial pressure (DAP) and MSNA in 15 healthy subjects at rest and during leg cycling in a seated position at fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
91
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(101 citation statements)
references
References 61 publications
(170 reference statements)
8
91
2
Order By: Relevance
“…Indeed, for the most part, studies using direct muscle SNA recordings, plasma norepinephrine as well as norepinephrine spillover have all suggested that sympathetic activation becomes progressively greater as exercise intensity and duration is increased (24,103,146,186). Galbo et al (103) reported a progressive increase in venous norepinephrine concentration during graded treadmill exercise at workloads above 50% maximal oxygen uptake (VO 2 max).…”
Section: Peripheral Sympathetic Activity During Steady-state Exercisementioning
confidence: 98%
“…Indeed, for the most part, studies using direct muscle SNA recordings, plasma norepinephrine as well as norepinephrine spillover have all suggested that sympathetic activation becomes progressively greater as exercise intensity and duration is increased (24,103,146,186). Galbo et al (103) reported a progressive increase in venous norepinephrine concentration during graded treadmill exercise at workloads above 50% maximal oxygen uptake (VO 2 max).…”
Section: Peripheral Sympathetic Activity During Steady-state Exercisementioning
confidence: 98%
“…In the present study, although there was a tendency for a blunted fall in SVR and BP at the onset of leg cycling exercise with glycopyrrolate, the lack of a strong effect perhaps signifies an effect of exercise modality on the mechanisms involved in control of circulatory responses. For example, a reduction in sympathetic vasoconstrictor neural outflow is documented at the onset of seated isometric quadriceps exercise (37) and low-intensity leg cycling (20) that may be secondary to activation of the cardiopulmonary baroreceptors resulting from an increase in venous return and right atrial pressure by the skeletal muscle pump (46,48). In contrast, sympathetic vasoconstrictor activity is typically unchanged at the onset of moderate intensity isometric handgrip and in- creases at higher handgrip intensities (26).…”
Section: Discussionmentioning
confidence: 99%
“…Despite that, the blood pressure fall in the early stage of one-leg extension (red arrow in Fig.3 (A)), and the prolonged decrease of the blood pressure during the one-leg cycling (between the red and green arrow in Fig.3 (B)) were observed in the experiment conducted by Radegran, et al, (1998), andSprangers, et al, (1991), respectively. In addition, the workloads in both cases are mild, which was defined in the previous study (Ichinose, et al (2008)). The auto-regulation mechanisms is responsible for the recovery of arterial pressure after the initial fall in arterial pressure during one-leg extension, which was also apparent in experimental data (Radegran, et al, (1998)).…”
Section: One-leg Extension and One-leg Cycling (Supine)mentioning
confidence: 99%
“…The CVS is influenced dynamically by the muscle pump and the metabovasodilation in terms of blood pressure, while the ANS is affected by a combination of the resetting of the operating pressure threshold of arterial baroreflex, central command model, and summary of mechanoreflex, metaboreflex and baroreflex. Here the oxygen intake (workload) is determined based on the previous studies (Ichinose, et al 2008;Melvin Keller, et al 2004;Papelier, et al 1994).…”
Section: Exercise Modelmentioning
confidence: 99%